ДО ПИТАННЯ ПРО ПІДВИЩЕННЯ ЕФЕКТИВНОСТІ ІНСТРУМЕНТАЛЬНО-ПРОФЕСІЙНОЇ ПІДГОТОВКИ МАЙБУТНЬОГО ВЧИТЕЛЯ МУЗИКИ ЗА МОДУЛЕМ «САМОСТІЙНЕ МУЗИКУВАННЯ» (Педагогіка вищої та середньої школи, 2007)
The article examines the essence of preparation of future teachers of music on the module «Self-Dependent Music Making», scientifically grounds and discovers methods that promote raising the efficiency of their formation.